2006
DOI: 10.1001/jama.296.9.1137
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessment in Lifelong Learning and Improving Performance in Practice

Abstract: Blueprint for establishing effective postbaccalaureate medical school pre-entry program for educationally disadvantaged students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
131
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(140 citation statements)
references
References 10 publications
(13 reference statements)
4
131
1
4
Order By: Relevance
“…24,25 Our finding that gender modified the association between knowledge and confidence is supported by previous findings that among undergraduate students, medical students, and residents, females tended to under-assess, and males tended to overassess their own competence. [26][27][28] Importantly, other studies have found that inaccurate self-assessment is most common among physicians with the least skills and greatest confidence, 25 raising concern that physicians and trainees who are newly adopting UDT may be ineffective at determining when they lack knowledge.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…24,25 Our finding that gender modified the association between knowledge and confidence is supported by previous findings that among undergraduate students, medical students, and residents, females tended to under-assess, and males tended to overassess their own competence. [26][27][28] Importantly, other studies have found that inaccurate self-assessment is most common among physicians with the least skills and greatest confidence, 25 raising concern that physicians and trainees who are newly adopting UDT may be ineffective at determining when they lack knowledge.…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, studies have found that physician self-assessment of knowledge in other clinical areas is often inaccurate. 24,25 Therefore, as part of a needs assessment about internal medicine residents' management of CNMP, we sought to explore the relationship between residents' knowledge and confidence in interpreting UDT results. We hypothesized that residents' knowledge and confidence in UDT interpretation would be low, and that they would be positively associated with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, objective data would be used in conjunction with iterative feedback, possibly through a mentor or advisor, to guide trainees when performing self-assessment. 5 Future studies might include reflection on individual or group data and should be done on a continuous basis with ongoing formative feedback, for example using a structured learning portfolio. 1,3 Validating the accuracy of residents' selfassessments, either singularly or through a learning portfolio, will be an ongoing challenge.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] In theory, self-assessment can serve as a mechanism for identifying one's strengths and weaknesses, and subsequently, identifying learning plans 1 and goals to improve patient care. 2 Reflective practice, which incorporates self-assessment, is a key component of professional development 6 and is being integrated into the evaluation of competency in residency training.…”
Section: Introductionmentioning
confidence: 99%
“…12 A growing body of evidence demonstrates relationships between certification status and quality of care including outcomes following acute MI, [13][14][15] colorectal surgery, 16 diabetes care, 17 mammography screening, 17 and other preventive services. 18 Unfortunately, unrelenting time pressures in clinical practice have made it increasingly difficult for physicians to maintain habits of lifelong learning, 19,20 resulting in decrements in medical knowledge over time. 9,21,22 Traditional continuing medical education (CME) courses vary in effectiveness [23][24][25] and often do not provide the "just in time" learning needed at the point of care.…”
mentioning
confidence: 99%